On a new species of the genus Zavrelimyia Fittkau, 1962 (Diptera: Chironomidae) from India with cladistic relationship and a world key to the known males - Mondal, Debarshi; Mukherjee, Tuhar; Hazra, Niladri (Zootaxa, 2022)
The adult male of Zavrelimyia (Paramerina) falcata sp.n. is described and illustrated from India. The DNA barcode of this new species is provided. The original description of Zavrelimyia (P.) valida (Paul, Hazra and Mazumdar, 2013) is corrected. The subgenus Schineriella Murray and Fittkau, 1988 of Zavrelimyia Fittkau is recorded in the Oriental region. A cladistic relationship of the species of Zavrelimyia Fittkau and a world key to the adult males of the genus Zavrelimyia Fittkau are provided.